Is Support for Feminism Enough for Change? How Sexism and Gender Stereotypes Might Hinder Gender Justice - Jiménez-Moya, Gloria; Carvacho, Héctor; Álvarez, Belén; Contreras, Camila; González, Roberto (Frontiers in Psychology, 2022)
Even though formal processes (i.e. gender quotes) are necessary to achieve gender justice, attitudinal changes (i.e. support of egalitarian social norms) are also essential. The endorsement of sexism and gender stereotypes perpetuate inequality on a daily basis, and can be seen as barriers that prevent societies from reaching social justice. Therefore, changing sexist social norms can be understood as a fundamental step in accomplishing gender justice. With the aim of studying Chileans’ sexist norms, we conducted a survey with a representative sample (N=490) exploring levels of sexism and gender stereotypes, as well as support for the feminist movement. Using Latent Profile Analysis we identified four groups of citizens: 1) a first group that shows high levels of sexism and low support for the feminist movement (9%); 2) a second group, with low levels of sexism and high support for the feminist movement (20%); 3) a third group with high levels of sexism and high support for the feminist movement (65%); and 4) a fourth group with mid-levels of sexism and support of the feminist movement (6%). We called these groups the Sexist, Feminist, Inconsistent and Moderate Group, respectively. The four groups showed similar high endorsement of gender stereotypes. These results are twofold. First, they hint that although nowadays gender equality seems to be generally accepted, this coexists with a high prevalence of sexist social norms, represented by the inconsistent group being the most prevalent. Second, gender stereotypes are still deeply rooted in Chilean culture, surprisingly even among feminist citizens.